Situation Report: Romania, 27 May 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Yugoslav-Romanian Friendship Albanian Ambassador Replaced Aftermath of the Comecon Meeting in Warsaw Economic Co-operation with the Soviet Union Coverage of Kassel Meeting Floods in Romania (II) Ceausescu's First Remarks on the Moscow Meeting